Laboratory-Based and Point-of-Care Testing for MSSA/MRSA Detection in the Age of Whole Genome Sequencing - van Belkum, Alex; Rochas, Olivier (Frontiers in Microbiology, 2018)
Staphylococcus aureus is an opportunistic pathogen of animals and humans that is capable of both colonizing and infecting its eukaryotic host. It is frequently detected in the clinical microbiology routine laboratory. S. aureus is capable of acquiring antibiotic resistance traits with ease and, given its rapid global dissemination, resistance to meticillin in S. aureus has received extensive coverage in the popular and medical press. The detection of meticillin-resistant versus meticillin-susceptible S. aureus (MRSA and MSSA) is of significant clinical importance. Detection of meticillin resistance is relatively straightforward since it is defined by a single determinant, penicillin-binding protein 2a’, which exists in a limited number of genetic variants carried on various Staphylococcal Cassette Chromosomes mec (SCCmec). Diagnosis of MRSA and MSSA has evolved significantly over the past decades and there has been a strong shift from culture-based, phenotypic methods towards molecular detection, especially given the close correlation between the presence of the mec genes and phenotypic resistance. This brief review summarizes the current state of affairs concerning the mostly PCR-mediated detection of MRSA and MSSA in either the classical laboratory setting or at the point of care. The potential diagnostic impact of the currently emerging whole genome sequencing (WGS) technology will be discussed against a background of diagnostic, surveillance and infection control parameters. Adequate detection of MSSA and MRSA is at the basis of any subsequent, more generic antibiotic susceptibility testing, epidemiological characterization and detection of virulence factors, whether performed with classical technology or WGS analyses.